Equity Partnership in joint enterprises by Islamic banks: Is a more equitable approach to sharing profit and loss possible? - Sadique, Muhammad Abdurrahman (2008)
According to Islamic guidelines on partnership ventures, the profit sharing ratio is determined at the outset, and the actual return to the partners is ascertained at the end on the basis of realised profits. In financing partnership ventures, Islamic banking usually fix the profit sharing ratio through applying the relevant rate of return on capital, taking into consideration the size of the bank’s investment and the period of the exposure. After first determining the return sought by the bank on its capital outlay, the remainder of the expected profit is usually taken as the share of the client / joint partner, and the proportion adopted as the ratio of profit sharing. Profit sharing ratio agreed in an ideal environment should bring about a fair share of the proceeds to each partner and adequately consider, among other factors, their actual contributions and the level of liability borne. The period, as a factor common to the joint venture and thus affecting both partners, could be redundant, and should not significantly influence the process. In the case of Islamic banks, in view of the socio-economic function they are supposed to perform, fixing the profit sharing ratio in joint ventures could not be regarded solely a business decision. As such, Islamic banks should be persuaded to adopt a method for profit ratio calculation that adequately considers the actual contributions of both the partners. Two bases possible are giving capital and labour equal weightage, considering profit to result from both equally, and giving each a weightage different from the other, considering the relative importance of each in the venture concerned.